Method for determining mineral content in high-temperature chlorination slag
Patent Information
- Application Number
- CN202611235628.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-23
AI Technical Summary
该类氯化渣中的焦炭存在形式并非完全是晶态,以非晶态形式的存在的焦炭也并不少见,而正是因为非晶的存在,导致利用XRD检测其矿物组成时往往不能做到准确定量
[0024]本发明提供了一种检测高温氯化渣样品中矿物含量的方法,具备较高的可行性和操作性,可以更好的掌握该类冶金渣样的准确矿物组成,准确测定高温氯化渣中的炭质含量,对判断冶金化合反应的进行程度和相关工艺的改进具备积极意义。
Smart Images

Figure CN122961840A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of analytical testing technology, and specifically relates to a method for determining the mineral content in high-temperature chlorination slag. Background Technology
[0002] Coke, as a key raw material in the metallurgical industry, plays an irreplaceable role in processes such as blast furnace ironmaking, titanium extraction from blast furnace slag, and high-temperature chlorination. In blast furnace ironmaking, coke serves as the main heat source and reducing agent, while also regulating the composition of molten iron; generally, no coke residue is found in the metallurgical blast furnace slag. However, in high-temperature chlorination processes, to ensure complete reaction, an excessive amount of coke is usually added. This results in varying amounts of residual coke in the chlorinated slag, the slag product after the reaction. This type of coke exists primarily in a free form, indicating a high degree of dissociation. Examples include coke particles of varying sizes commonly found in metallurgical slags such as molten salt chlorination slag, fluidized bed chlorination slag, and SR synthetic rutile selective chlorination slag, which are largely unattached to other minerals. The raw materials for this type of metallurgical slag are generally titanium-rich materials, titanium slag, and titanium concentrate, with mineral composition mainly consisting of rutile, diatomite, silicate minerals, and ilmenite. The phases in the chlorinated slag after high-temperature chlorination are generally dominated by residual diatomite, rutile, silicate minerals, and coke. The coke in this type of chlorinated slag is not entirely crystalline; coke in amorphous form is also quite common. It is precisely because of the presence of amorphous coke that accurate quantitative analysis of its mineral composition using XRD is often impossible.
[0003] Even when using existing mineral analyzers to detect its composition, complete quantification is not possible. The results generally do not include the composition and content of coke. This is because the grayscale value of the epoxy resin background of the solidified sample under electron beam electron microscopy is very close to that of coke. Therefore, mineral analysis software automatically subtracts it as background during data acquisition, resulting in the omission of coke composition in the final result. However, researchers often need to obtain information on the composition and content of all minerals in the sample to better assess the progress of the reaction and determine whether relevant process parameters need to be adjusted. But the results obtained from actual tests are often inaccurate.
[0004] Therefore, it is necessary to develop a method that can accurately detect the mineral content of high-temperature chlorinated slag. Summary of the Invention
[0005] The purpose of this invention is to provide a method for determining the mineral content in high-temperature chlorination slag, so as to obtain the accurate mineral composition of such samples.
[0006] To achieve the above objectives, the present invention provides a method for determining the mineral content in high-temperature chlorination slag, comprising the following steps:
[0007] A. The high-temperature chlorination slag is crushed and ground to obtain a powder sample;
[0008] B. Weigh an appropriate amount of powder sample, record the mass as m, press it into a thin sheet, place it in a tube furnace, connect a metal conduit to the outside of the tube furnace to discharge gas in time, connect the end of the conduit to the first gas washing bottle, the first gas washing bottle contains a sodium hydroxide aqueous solution with a mass fraction of 15~25%, connect the end of the first gas washing bottle to the second gas washing bottle, the second gas washing bottle contains a sodium hydroxide aqueous solution with a mass fraction of 15~25%, connect the end of the second gas washing bottle to the drying bottle, the drying bottle contains phosphorus pentoxide or silica gel;
[0009] C. Introduce oxygen into the tubular furnace and control the gas flow rate to 100~200ml / min to remove air from the tubular furnace, gas washing bottle and drying bottle. Record the initial total mass of the first and second gas washing bottles and the drying bottle at this time.
[0010] D. Reduce the gas flow rate to 50~100ml / min, continue to introduce oxygen, heat the tubular furnace to 800~900℃, and keep it at this temperature until the pH of the solution in the first and second gas washing bottles is stable and unchanged. Record the total mass of the first and second gas washing bottles and the drying bottle at this time.
[0011] E. By measuring the mass changes of the first and second gas washing bottles and the drying bottle before and after the reaction, the mass of carbon dioxide gas absorbed by the sodium hydroxide aqueous solution is obtained and converted into the mass of pure carbon m1. Then, the content percentage of coke in the sample is a = m1 / m × 100%, and the content percentage of other components besides coke is b = (m - m1) / m × 100%.
[0012] F. Prepare a reflective sheet from high-temperature chlorination slag and use a mineral analyzer to detect the types and contents of components other than coke in the high-temperature chlorination slag.
[0013] G. By converting the coke content percentage (a), the other component content percentage (b), and the other component types and contents obtained from the mineral analyzer, we can obtain the composition and content of all minerals in the high-temperature chlorinated slag.
[0014] In the above determination method, in step A, the particle size of the powder sample is 100~300 mesh.
[0015] In the above-mentioned measurement method, step B involves pressing the material into a thin sheet with a diameter of 1-5 cm.
[0016] In the above-mentioned measurement method, in step B, a water-cooling sleeve is installed on the outside of the metal conduit.
[0017] In the above-mentioned determination method, in step B, the first and second gas washing bottles are made of rubber stoppers and PTFE tubing. The PTFE tubing is submerged below the liquid surface. A pH electrode is inserted into the gas washing bottle, and the electrode is submerged below the liquid, not close to the bottle wall, and far away from the impact position of the incoming air bubbles.
[0018] In the above determination method, in step B, the ratio of sodium hydroxide aqueous solution to powder sample in the first gas washing bottle is 100 mL: 5~15 g.
[0019] In the above determination method, in step B, the ratio of sodium hydroxide aqueous solution to powder sample in the second gas washing bottle is 100 mL: 5~15 g.
[0020] In the above-mentioned determination method, in step C, the oxygen introduction time is 2-5 minutes.
[0021] In the above-mentioned determination method, the high-temperature chlorination slag is the metallurgical slag used in the fluidized bed chlorination process, molten salt chlorination process, and SR artificial rutile selective chlorination process.
[0022] The mineral components in the high-temperature chlorinated slag, as determined by the above-mentioned method, include coke, rutile, diatomite, pyroxene, aluminosilicate, alumina, and quartz.
[0023] The beneficial effects of this invention are:
[0024] This invention provides a method for detecting the mineral content in high-temperature chlorination slag samples. It has high feasibility and operability, and can better grasp the accurate mineral composition of this type of metallurgical slag sample and accurately determine the carbon content in high-temperature chlorination slag. This has positive significance for judging the degree of metallurgical chemical reaction and improving related processes. Attached Figure Description
[0025] Figure 1 This is an electron micrograph of coke in a molten salt high-temperature chlorination slag sample.
[0026] Figure 2 This is a diagram of the apparatus used in this invention to determine the mineral content in high-temperature chlorinated slag. Detailed Implementation
[0027] Specifically, a method for determining the mineral content in high-temperature chlorination slag includes the following steps:
[0028] Step 1: Crush and grind the high-temperature chlorination slag to 100-300 mesh to obtain the corresponding powder sample. In this invention, the high-temperature chlorination slag mainly comes from metallurgical slag products of high-temperature chlorination processes, such as fluidized bed chlorination, molten salt chlorination, and SR synthetic rutile selective chlorination processes. Typical electron micrographs are shown below. Figure 1 As stated above.
[0029] Step 2: Weigh an appropriate amount of powder sample, denoted as m, and press it into a thin sheet with a thickness of 1-5 cm using a tablet press. Place the sheet into a tube furnace, with a metal conduit connected to the outside of the furnace to facilitate timely gas discharge. The metal conduit should be of appropriate length and fitted with a water-cooling sleeve to maintain the gas temperature flowing into the washing bottle at approximately room temperature, ensuring the carbon dioxide absorption rate. Connect the end of the conduit to a PE plastic first washing bottle, which contains a 15-25% sodium hydroxide aqueous solution. Connect the end of the first washing bottle to a second washing bottle, which also contains a 15-25% sodium hydroxide aqueous solution. Use rubber stoppers and PTFE conduits for both the first and second washing bottles, with the PTFE conduit submerged below the liquid surface. Insert a pH electrode into the washing bottle, submerged below the liquid surface but not close to the bottle wall or the point of impact from incoming air bubbles. Connect the end of the second washing bottle to a drying bottle, which contains phosphorus pentoxide or silica gel. Place the first, second, and third washing bottles and the drying bottle on a suitable digital electronic balance for real-time recording of mass changes.
[0030] In this invention, the residual coke content of the high-temperature chlorination slag is generally less than 10%. The ratio of sodium hydroxide aqueous solution to powder sample in the first gas washing bottle is controlled at 100mL: 5~15g; the ratio of sodium hydroxide aqueous solution to powder sample in the second gas washing bottle is also 100mL: 5~15g. The experimentally tested sodium hydroxide aqueous solution with a mass fraction of 15~25% not only has strong adsorption capacity and moderate water content, but also suitable solution viscosity, which is conducive to bubble dispersion and absorption. The cost is low, and it ensures that carbon dioxide is completely absorbed and does not escape, does not produce sodium bicarbonate, and has sufficient alkali residue in the solution. Under normal circumstances, the first gas washing bottle can completely absorb the carbon dioxide, and the second gas washing bottle mainly serves as a verification. After the reaction is complete, a calcium chloride aqueous solution with a mass fraction of 5~15% can be added. If a white precipitate appears, it indicates that the first gas washing bottle has not completely absorbed the carbon dioxide produced by roasting; otherwise, it indicates complete absorption. However, in most cases, a white precipitate will not appear. The purpose of the drying bottle is to absorb the moisture in the gas washing bottle that may be carried away by the excess oxygen atmosphere passing through it, thereby reducing experimental errors.
[0031] Step 3: Pre-purge oxygen into the tubular furnace at a flow rate of 100-200 ml / min for 2-5 minutes to remove as much air as possible from the tubular furnace and the washing and drying bottles containing sodium hydroxide solution. Record the initial total mass (including sodium hydroxide solution and desiccant) of the first and second washing bottles and the drying bottle at this time.
[0032] Step 4: Reduce the oxygen flow rate to 50-100 ml / min to further reduce the amount of moisture carried away from the washing bottles by the rapid airflow. Continue to introduce oxygen and heat the tubular furnace to 800-900℃. Maintain this temperature until the pH value of the solution in the first and second washing bottles is basically stable and unchanged. Record the total mass of the first and second washing bottles and the drying bottle (including sodium hydroxide aqueous solution and desiccant) at this point. In this invention, the high-temperature chlorination slag is crushed and ground. After extensive observation by electron microscopy, it was found that the coke in this type of high-temperature chlorination slag exists primarily in a free, monomeric state, with a small amount of particles intergrowth with other minerals. The edge length of the intergrowth is relatively short, and there are basically no completely encapsulated coke particles. Therefore, under the reaction conditions of this invention, the coke in the sample can achieve complete reaction, ensuring the accuracy of the detection results.
[0033] Step 5: By measuring the mass changes of the first and second gas washing bottles and the drying bottle before and after the reaction, obtain the mass of carbon dioxide gas absorbed by the sodium hydroxide aqueous solution and convert it into the mass of pure carbon m1. Then, the content percentage of coke in the sample is a = m1 / m × 100%, and the content percentage of other components besides coke is b = (m - m1) / m × 100%.
[0034] Step 6: Select an appropriate amount of high-temperature chlorination slag and prepare it into a reflective sheet. Use a mineral analyzer to detect the types and contents of the components other than coke in the high-temperature chlorination slag.
[0035] Step 7: Integration and Calculation—Convert the coke content percentage (a), the other component content percentage (b), and the other component types and contents obtained from the mineral analyzer to obtain the component types and contents data of all minerals in the high-temperature chlorination slag; the mineral components in the high-temperature chlorination slag include coke, rutile, diatomite, pyroxene, aluminosilicate, alumina, and quartz.
[0036] Step six of this invention employs a conventional method in the field for detecting mineral composition and content using a mineral analyzer. The mineral analyzer testing operation and steps are as follows: 1. The high-temperature chlorinated slag sample is cold-mounted and solidified into a reflective sheet using epoxy resin and a curing agent, and then ground and polished to obtain a qualified reflective sheet sample (the sheet sample diameter is 3cm and the thickness is about 1cm); 2. The sheet sample is subjected to spray coating treatment, and then the sample is placed in the sample chamber of the mineral analyzer, and the vacuum is drawn to 3×10 -43. After vacuum preparation, apply high voltage to the electron microscope. Select 25kV for the high voltage, 40μA for the current, and 7.40 for the beam spot. Use a copper standard sample to calibrate the background brightness and contrast. Select a background subtraction threshold of approximately 120. 4. Adjust the sample focal length to approximately 10mm. Select an image resolution of 512×400 for the acquisition software, a magnification of 500x for the electron microscope, a frame rate of 500 frames or a minimum of 100,000 mineral particles, an energy dispersive spectroscopy (EDS) time parameter of 1.6, an EDS count rate of approximately 75,000, and a dead time of approximately 27. 5. After parameter settings are complete, the equipment will automatically acquire data until it automatically ends. 6. Combine the data obtained from the mineral database built into the mineral analyzer and conventional metallurgical mineral databases in this field to name the minerals. Finally, the mineral analysis software built into the mineral analyzer will calculate the mineral composition and content data. Note: The gray value of coke under an electron microscope is close to that of the sample background—that is, epoxy resin. When the mineral acquisition software performs sample background subtraction, it will directly treat it as the background and subtract it. Therefore, the data obtained by the mineral analyzer test does not contain coke.
[0037] In this invention, an apparatus for determining the mineral content in high-temperature chlorination slag is provided. Figure 2 As shown, it is a conventional device in this field and can be built independently.
[0038] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.
[0039] The starting compounds, raw materials and / or reagents used in the reactions described in this invention can be obtained through legitimate commercial channels or prepared by methods reported in chemical literature.
[0040] Example 1
[0041] Step 1: Crush and grind the high-temperature chlorination slag to 200 mesh to obtain the corresponding powder sample.
[0042] Step Two: Weigh an appropriate amount of powder sample, denoted as m, and press it into a thin sheet with a thickness of 1-5 cm using a tablet press. Place the sheet into a tube furnace, with a metal conduit connected to the outside of the furnace for timely gas discharge. A water-cooling sleeve is fitted to the outside of the metal conduit. The end of the conduit is connected to a PE plastic first gas washing bottle, which is then connected to a second gas washing bottle. Both the first and second gas washing bottles contain a 15-25% sodium hydroxide aqueous solution. The first and second gas washing bottles use rubber stoppers and PTFE conduits, with the PTFE conduits submerged below the liquid surface. A pH electrode is inserted into the gas washing bottle, submerged below the liquid surface, not close to the bottle wall, and away from the impact point of the incoming air bubbles. The second gas washing bottle is connected to a drying bottle containing phosphorus pentoxide or silica gel. The first, second, and third gas washing bottles and the drying bottle are placed on a suitable digital display electronic balance for real-time recording of mass changes.
[0043] Step 3: Pre-purge oxygen into the tubular furnace at a flow rate of 100-200 ml / min for 2-5 minutes to remove as much air as possible from the furnace and from the washing bottles and drying bottles containing sodium hydroxide solution. Record the initial total mass of the first and second washing bottles and the drying bottle at this point.
[0044] Step 4: Continuously introduce an oxygen atmosphere, reducing the oxygen flow rate to 50-100 ml / min to minimize the removal of moisture from the washing bottles due to excessive airflow. Heat the solution in the tube furnace to 800-900℃ and maintain this temperature until the pH values of the solutions in the first and second washing bottles are essentially stable and unchanged. Record the total mass of the first and second washing bottles and the drying bottle at this point.
[0045] Step 5: By measuring the mass changes of the first and second gas washing bottles and the drying bottle before and after the reaction, obtain the mass of carbon dioxide gas absorbed by the sodium hydroxide solution and convert it into the mass of pure carbon m1. Then, the content percentage of coke in the sample is a = m1 / m × 100%, and the content percentage of other components besides coke is b = (m - m1) / m × 100%.
[0046] Step 6: Select an appropriate amount of chlorinated slag sample and prepare it into a reflective sheet. Use a mineral analyzer to test the types and contents of the components other than coke.
[0047] Step 7: Integration and Calculation—Convert the coke content percentage 'a', the other component content percentage 'b', and the other component types and contents obtained from the mineral analyzer to obtain the component types and contents data of all minerals in the entire sample.
[0048] The specific steps are as follows:
[0049] Adopting such Figure 2The apparatus diagram shows the process of weighing 10g of a high-temperature chlorination slag sample, grinding and mixing it, pressing it into a thin sheet with a diameter of 3cm, and placing it in a tube furnace. The atmosphere inside the tube furnace is oxygen. Both the first and second gas washing bottles contain 100ml of a 20% sodium hydroxide aqueous solution. The remaining settings and conditions are as in step two. The oxygen flow rate is set to 150ml / min, and the time for purging air from the gas washing and drying bottles is set to 3min. After purging the air, the oxygen flow rate is reduced to 60ml / min. The tube furnace is heated to 850℃ and kept constant. The total mass difference between the first and second gas washing bottles and the drying bottle before and after calcination is 1.91g, meaning that the sodium hydroxide solution absorbed 1.91g of carbon dioxide gas, which is equivalent to 0.52g of pure carbon. This indicates that the content of coke in the original sample is a=5.20%, and the content of the remaining components in the sample is b=94.8%. The remaining mineral component content data obtained using a mineral analyzer (model: MLA650, equipment manufacturer: FEI Corporation, USA) are shown in Table 1. All data were integrated and processed to obtain the final mineral composition of the high-temperature chlorination slag sample, as shown in Table 1.
[0050] Table 1. Mineral composition and content (%) of high-temperature chlorination slag
[0051]
[0052] Based on the sample coke content of 5.20% measured in Table 1, this was recorded as the background coke content of the sample. Using this as a blank control, three spiking gradients were set up from low to high: adding 1.5% standard coke, adding 3.0% standard coke, and adding 5.0% standard coke. This resulted in the theoretical total coke content of the three spiked samples being 6.70%, 8.20%, and 10.20%, respectively. Three parallel experiments were set up for each gradient spiking group.
[0053] Experimental Procedure: 1. Take an appropriate amount of the original sample, grind it to 200 mesh, and mix thoroughly for later use. 2. Accurately weigh 10g of the original sample prepared in step 1 into nine groups, and mix it with coke standard samples (0.1608g, 0.3268g, 0.5568g) according to the set spiking gradient. Grind to 200 mesh and mix thoroughly to ensure homogeneity and no segregation. Prepare three gradient spiking samples. 3. Conduct the test on the spiked samples according to the aforementioned operation method, and measure the total coke content in each spiked sample. 4. Perform three parallel tests for each spiking gradient, and take the average value as the measured value of each group. 5. Coke recovery rate calculation formula: Coke recovery rate (%) = [(10g + spiking amount) × measured total coke content after spiking - 0.52g)] / spiking amount × 100%. 6. Criteria for acceptance: Referring to the industry standard for spiked recovery rate of solid mineral samples (DZ / T 0130.3-2006 "Quality Management Specifications for Geological and Mineral Laboratory Testing Part 3: Chemical Composition Analysis of Rock and Mineral Samples"): Major components (mass fraction 1~10%): 90%~110%. If the result is within this range, it indicates that the test method used in this invention is accurate in quantifying coke, has no systematic bias, and is reliable.
[0054] Experimental Results: 1. With a spiked amount of 0.1608g, the measured total coke content after spiked addition was 6.68%. Therefore, the coke recovery rate = [(10g + 0.1608g) × 6.68% - 0.52g)] / 0.1608g × 100% = 98.7%. 2. With a spiked amount of 0.3268g, the measured total coke content after spiked addition was 8.15%. Therefore, the coke recovery rate = [(10g + 0.3268g) × 8.15% - 0.52g)] / 0.3268g × 100% = 98.4%. 3. With a spiked amount of 0.5568g, the measured total coke content after spiked addition is 10.12%. Therefore, the coke recovery rate = [(10g + 0.5568g) × 10.12% - 0.52g)] / 0.3268g × 100% = 98.5%. 4. The average coke recovery rate = (98.7 + 98.4 + 98.5) / 3 × 100% = 98.5%. All results are within the acceptable range of 90-110%, proving that the results of this invention are accurate and reliable.
[0055] Coke content precision test: 1. Divide the same homogeneous original sample into 6 independent parallel tests. Determine the coke content in each sample independently according to the above procedure, and calculate the average value, standard deviation, and relative deviation. Acceptance criteria: Refer to industry-standard specifications (General Industry Quality Control Specifications for Coal Chemical and Metallurgical Solid Waste Testing, GB / T 3521-2008 "Graphite Chemical Analysis Methods", DZ / T 0130.3-2006 "Geological and Mineral Laboratory Testing Quality Management Specifications Part 3: Chemical Composition Analysis of Rock and Mineral Samples", GB / T 20899.9-2025 "Gold Ore Chemical Analysis Methods Part 9: Determination of Carbon Content"). For coke content levels of 5-6%, a general RSD ≤ 3.0% is considered acceptable. High-precision quantitative analysis generally requires an RSD ≤ 2.0%.
[0056] The measured results of coke content are shown in Table 2.
[0057] Table 2. Results of Coke Content Detection / %
[0058]
[0059] Calculate the average value =5.20%, standard deviation S=0.065, RSD=1.26%. The results show that the relative standard deviation of the parallel test of the whole process of the present invention is 1.26%, which is less than the industry allowable error threshold of 3.0% and also less than the error threshold of 2.0% required for high-precision quantification. This indicates that the present invention has good repeatability, small random error and reliable precision for coke content detection.
Claims
1. A method for determining the mineral content in high-temperature chlorination slag, characterized in that: Includes the following steps: A. The high-temperature chlorination slag is crushed and ground to obtain a powder sample; B. Weigh an appropriate amount of powder sample, record the mass as m, press it into a thin sheet, place it in a tube furnace, connect a metal conduit to the outside of the tube furnace to discharge gas in time, connect the end of the conduit to the first gas washing bottle, the first gas washing bottle contains a sodium hydroxide aqueous solution with a mass fraction of 15~25%, connect the end of the first gas washing bottle to the second gas washing bottle, the second gas washing bottle contains a sodium hydroxide aqueous solution with a mass fraction of 15~25%, connect the end of the second gas washing bottle to the drying bottle, the drying bottle contains phosphorus pentoxide or silica gel; C. Introduce oxygen into the tubular furnace and control the gas flow rate to 100~200ml / min to remove air from the tubular furnace, gas washing bottle and drying bottle. Record the initial total mass of the first and second gas washing bottles and the drying bottle at this time. D. Reduce the gas flow rate to 50~100ml / min, continue to introduce oxygen, heat the tubular furnace to 800~900℃, and keep it at this temperature until the pH of the solution in the first and second gas washing bottles is stable and unchanged. Record the total mass of the first and second gas washing bottles and the drying bottle at this time. E. By measuring the mass changes of the first and second gas washing bottles and the drying bottle before and after the reaction, the mass of carbon dioxide gas absorbed by the sodium hydroxide aqueous solution is obtained and converted into the mass of pure carbon m1. Then, the content percentage of coke in the sample is a = m1 / m × 100%, and the content percentage of other components besides coke is b = (m - m1) / m × 100%. F. Prepare a reflective sheet from high-temperature chlorination slag and use a mineral analyzer to detect the types and contents of components other than coke in the high-temperature chlorination slag. G. By converting the coke content percentage (a), the other component content percentage (b), and the other component types and contents obtained from the mineral analyzer, we can obtain the mineral composition and content in the high-temperature chlorinated slag.
2. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step A, the particle size of the powder sample is 100~300 mesh.
3. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step B, the material is pressed into thin sheets with a diameter of 1-5 cm.
4. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step B, a water-cooling sleeve is installed on the outside of the metal conduit.
5. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step B, the first and second gas washing bottles are fitted with rubber stoppers and PTFE tubing. The PTFE tubing is submerged below the liquid surface. A pH electrode is inserted into the gas washing bottle, submerged below the liquid, not close to the bottle wall, and far away from the impact point of the incoming air bubbles.
6. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step B, the ratio of sodium hydroxide aqueous solution to powder sample in the first gas washing bottle is 100 mL: 5~15 g.
7. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step B, the ratio of sodium hydroxide aqueous solution to powder sample in the second gas washing bottle is 100 mL: 5~15 g.
8. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: In step C, the oxygen is introduced for 2 to 5 minutes.
9. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: High-temperature chlorination slag is the metallurgical slag used in fluidized bed chlorination, molten salt chlorination, and SR synthetic rutile selective chlorination processes.
10. The method for determining the mineral content in high-temperature chlorination slag according to claim 1, characterized in that: The mineral components in high-temperature chlorination slag include coke, rutile, diatomite, pyroxene, aluminosilicate, alumina, and quartz.